Preclinical Research in Treatment of Pancreatic Cancer - Skoura, Evangelia; Syrigos, Konstantinos N; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2013)
Pancreatic adenocarcinoma is an aggressive type of malignancy and remains a treatment-refractory cancer. Because of the few treatment options, understanding of the molecular mechanisms is necessary, for new drugs be developed against molecular targets. Two of the novel, promising regimens against molecular targets, NVP-BEZ235 and MSK-777, were examined in three preclinical studies performed in human pancreatic cell lines and mouse models and presented in the 2013 ASCO Annual Meeting. Two of the studies evaluated the role of NVP-BEZ235, an oral phosphatidylinositol-3-kinase (PI3K) inhibitor, in pancreatic cancer treatment, alone and in combination with nab-paclitaxel (Abstract #e15007) or gemcitabine (Abstract #e15070). The third study presents the effectiveness of the novel cell division cycle 7 (Cdc7) kinase inhibitor, MSK-777 (Abstract #e15059). All studies demonstrated promising results and further investigation is ongoing. Image: PI3K-AKT-mTOR signalling pathway.